Analisis Yuridis Pemanfaatan Internet Banking dalam Pembayaran Menggunakan Letter of Credit pada Perdagangan Ekspor Impor - Marewa, Yeheschiel Bartin (Kainawa: Jurnal Pembangunan dan Budaya, 2024)
This research aims to understand the Letter of credit system with the main focus of this research being how to use the Letter of credit system in Import Export Trade and how to protect it legally. This research is library law research. The data collection method was carried out using literature study (legal memorandum) and interviews as supporting data. The collected data is then presented in the form of narrative text which is arranged systematically. L/C is the most widely used payment instrument in export-import transactions. Apart from being easy, L/C is also guaranteed because it cannot be cancelled, customer protection must comply with the provisions: Uniform Customs and Practice for Documentary Credits, Revised 2007, ICC Publication No. 600 (UCP) which is a provision that applies to every documentary credit and ISBP (International Standard Banking Practice) which is one of the rules that applies worldwide regarding the operational implementation of L/C (Letter of Credit).